REWARDS, PUNISHMENTS, AND EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF DISCIPLINE IN CREDIT UNIONS IN WEST KALIMANTAN - Bertus AS, Adil; Elvi, Fitria; Masiun, Stefanus (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Good performance reflects staff effectiveness at work, which can be achieved through disciplined behavior. However, disciplined behavior is shaped by policies related to rewards and punishments for staff. The purpose of this study is to examine the impact of rewards and punishments on the performance of Credit Union staff, with discipline as a mediating factor. The sample in this study consisted of 160 staff members from 78 branches of the Credit Union. The method employed was SEM-PLS 4.0. The findings demonstrate that disciplined behavior has a significant effect on staff performance, and the implementation of punishment significantly affects staff discipline. However, punishment does not directly influence performance, meaning it alters disciplined behavior but does not immediately improve work outcomes. Indirectly, however, punishment, through its effect on discipline, significantly influences staff performance. Meanwhile, the reward system implemented does not affect either disciplinary behavior or staff performance at Credit Union. Furthermore, indirectly, the reward system mediated by discipline also shows no significant effect on staff performance. The novelty of this study lies in the finding that the punishment system has a significant indirect effect on performance through discipline, whereas rewards do not exert any influence, either directly or indirectly. This finding challenges the prevailing assumption in human resource management, which tends to position rewards as the primary driver of performance improvement, particularly within the context of Credit Union organizations.